Data from: Impact of winter enclosures on the gut bacterial microbiota of red deer in the Bavarian Forest National Park - Menke, Sebastian; Heurich, Marco; Henrich, Maik; Wilhelm, Kerstin; Sommer, Simone (Dryad, 2019)
High numbers of red deer (Cervus elaphus) pose a challenge for natural
forests because of their high browsing intensities, especially during
winter months. To mitigate this human–wildlife conflict, conservation
management in Central Europe involves luring red deer into fenced
winter-feeding sites. The supplementary diet provided in these so-called
winter enclosures strongly differs from the natural diet of red deer.
Dietary shifts, however, can lead to an imbalance of the gut microbiota,
which could promote bacterial pathogens. Moreover, increased
inter-individual contact in winter enclosures enhances the exchange of
symbiotic but also pathogenic bacteria. In this study, we used
high-throughput sequencing of the 16S rRNA gene in fecal samples of red
deer inhabiting the Bavarian Forest National Park to investigate
differences in the gut bacterial microbiota between individuals in winter
enclosures and individuals that ranged freely in the forests in winter. We
also investigated the occurrence of potential zoonotic bacterial pathogens
in both study groups. Our results revealed that proportions of bacterial
taxa, alpha- and beta-diversities, and relative abundances of amplicon
sequence variants in the gut bacterial microbiota of the two groups
differed. These differences were attributed to the enrichment of bacterial
taxa involved in the digestion of the supplementary food and to different
natural diets consumed before entering the winter enclosures. We detected
sequences with high similarities to known red deer pathogens in both study
groups, but their relative abundances were low, which suggests that the
population of red deer of the National Park Bavarian Forest is healthy.
red_deer_microbiome_16S
Keywords: supplementary feeding; Cervus elaphus; red deer; winter enclosure; gut bacterial microbiome